1997
DOI: 10.1007/s004210050231
|View full text |Cite
|
Sign up to set email alerts
|

Arterial blood pressure and forearm vascular conductance responses to sustained and rhythmic isometric exercise and arterial occlusion in trained rock climbers and untrained sedentary subjects

Abstract: Cardiovascular responses to sustained and rhythmic (5 s on, 2 s off) forearm isometric exercise to fatigue at 40% maximal voluntary contraction (MVC) and to a period of arterial occlusion were investigated in elite rock climbers (CLIMB) as a trained population compared to non-climbing sedentary subjects (SED). Blood pressure (BP), monitored continuously by Finapres, and forearm blood flow, by venous occlusion plethysmography, were measured and used to calculate vascular conductance. During sustained exercise, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
4
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 14 publications
(21 reference statements)
8
86
4
1
Order By: Relevance
“…Further investigations are needed to determine if this conclusion is also valid for the wrist adduction-abduction and the forearm pronation-supination muscle groups. In a similar way, the capacities of climbers' intrinsic hand muscles were not significantly higher which is in accordance with the studies which demonstrated that climbers do not achieve higher performances for non-specific climbing tasks such as hand dynamometer tests (Ferguson and Brown 1997). To sum up, this study demonstrates that current climbing practice and training methods do not result in homogeneous improvements of muscle capacities, since only finger flexors are enhanced without modifications of other hand and wrist muscles.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Further investigations are needed to determine if this conclusion is also valid for the wrist adduction-abduction and the forearm pronation-supination muscle groups. In a similar way, the capacities of climbers' intrinsic hand muscles were not significantly higher which is in accordance with the studies which demonstrated that climbers do not achieve higher performances for non-specific climbing tasks such as hand dynamometer tests (Ferguson and Brown 1997). To sum up, this study demonstrates that current climbing practice and training methods do not result in homogeneous improvements of muscle capacities, since only finger flexors are enhanced without modifications of other hand and wrist muscles.…”
Section: Discussionsupporting
confidence: 90%
“…Diff EMG represents the mean (among all tasks and all subjects of a population) of the differences between the estimated mechanical activity of each muscle group and the recorded EMG activity. Ferguson and Brown 1997;Grant et al 2003;Quaine et al 2003) or iso-kinetic exercises (Schweizer and Furrer 2007). These studies reported the results of external torques and forces measured during the tests and brought interesting knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the relatively small amount of activated skeletal muscle in the forearms, the lack of relationship between conduit artery (brachial) blood flow and performance is not surprising and supports previous -albeit more indirect -findings. The earlier studies reported that forearm vascular conductance is higher in trained rock climbers compared to a control group after both sustained and intermittent handgrip exercise, as well as post 10 min arterial occlusion (Ferguson and Brown 1997). …”
Section: Discussionmentioning
confidence: 95%
“…For instance, in the study by Watts et al (6) previously mentioned, the authors did not verify significant differences of MHS between the semifinalists and finalists of a qualifying of the Sport Climbing World Cup. In another subsequent study, Fergunson and Brown (7) observed that the MHS of a group of elite climbers did not differ either from a sedentary group. However, in this investigation the TBM of the subjects was not measured, which made the assessment of the MHS in relation to the TBM impossible.…”
Section: Morphological and Handgrip Strength Characteristics Of Sportmentioning
confidence: 87%